DOPING AND PENALTY CONFLICT (Journal of Pharmaceutical Negative Results, 2022)
The aim of this study is to examine the criminal dimension in doping from a legal perspective. As a result of this examination, answers were sought to questions such as whether doping athletes are subject to a criminal procedure in general law, if so, how effective or applied, what are the contradictions between legal disciplines. In this study, in terms of general law and sports law, the conflict of the penalties given by the two legal disciplines within their own dynamics in doping is, more clearly, the fact that each branch of law treats the issue with its own perspective and the resulting contradictions. According to Article 162b of the Norwegian General Penal Code, any person who sends, imports, exports, sells, transports, manufactures any substance that is considered doping illegally will be charged with a doping offense and will be prosecuted with a sentence of 2 to 6 years in prison. While there is such an example in the world, such a legal system has not yet been established in Turkey. As a result, in Turkey, it is urgently necessary to ensure that general law and sports law meet on a common ground with the doping law to be prepared by experts in doping, and the federations should prepare their own internal regulations regarding doping based on this law.